2015
DOI: 10.1007/s10311-015-0521-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher cytotoxicity and genotoxicity of burning incense than cigarette

Abstract: Hazardous particulates and volatiles produced by incense burning accumulate in the indoor atmosphere, where they pose a health risk, entering the human body via the respiratory system. Yet, few studies have focused on the effects of the total particulate matter from incense burning on human health. Here, we evaluate the health risks associated with the total particulate matter generated from burning incense indoors for the first time. The total particulate matter and major chemical components of two types of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…There were no indoor PM-bound EC sources in Salon 1; its high indoor level was due to the accumulation of outdoor PM-bound EC. At Salon 4, where burning of scented candles and incense sticks (almost all the time during opening hours) was an effective indoor source of PM and PM-bound EC (Knight et al 2001;Gupta and Bhandari 2011;Manoukian et al 2013;Kumar et al 2014;Zhou et al 2015Zhou et al , 2016Goel et al 2017), the PM-bound EC originating from indoor sources prevailed over that from outdoors. This made the differences between the indoor and outdoor 8-h concentrations for both PM 4 -bound EC and TPM-bound EC statistically significant (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…There were no indoor PM-bound EC sources in Salon 1; its high indoor level was due to the accumulation of outdoor PM-bound EC. At Salon 4, where burning of scented candles and incense sticks (almost all the time during opening hours) was an effective indoor source of PM and PM-bound EC (Knight et al 2001;Gupta and Bhandari 2011;Manoukian et al 2013;Kumar et al 2014;Zhou et al 2015Zhou et al , 2016Goel et al 2017), the PM-bound EC originating from indoor sources prevailed over that from outdoors. This made the differences between the indoor and outdoor 8-h concentrations for both PM 4 -bound EC and TPM-bound EC statistically significant (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Incense burning generates a complex mixture of gases and particulate matter, which is known to be deleterious to human health [11, 12]. In fact, an in-vitro study has shown that the genotoxicity of particulate matter from incense burning could be higher than that from cigarette smoke [13]. Epidemiological studies suggest that incense use is associated with elevated blood pressure [6], and higher risks of cardiovascular disease morbidity and mortality [7, 14], upper respiratory tract cancers [15], and nasopharyngeal cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have linked incense burning with damages to pneumocytes . An in vitro experiment also showed that incense smoke could induce cytotoxicity and genotoxicity . Some epidemiological studies have also investigated the health effects of incense burning, mainly on the respiratory system, but the results are inconsistent .…”
Section: Introductionmentioning
confidence: 99%